The Role of Eye Color in the Emergence of Tinnitus in Silence - Onyinyechi C. Ukaegbe (Thieme Revinter Publicações Ltda., 2021)
Introduction Previous research suggests that African Americans are less likely than Caucasians to perceive tinnitus in sustained silence. Objective To evaluate the association between non-cutaneous melanin as indicated by eye color and the emergence of temporary tinnitus during a brief period of silence. Methods A cross-section of adults grouped according to their eye color were exposed to silence. A total of 62 adults, aged 18 to 35 years (10 males, 52 females) were required to sit in silence for 10 minutes, after which they filled out a questionnaire to report their eye color and any perception of sounds in the ears or head. Results In total, 63% of the participants perceived tinnitus while sitting in silence, and, of these 95% perceived the tinnitus sounds within 5 minutes of sitting in silence. Though African Americans were less likely to perceive tinnitus in silence, this difference was not significant (p = 0.6). After a period of silence, 69% of the subjects with light-colored eyes and 58% of the dark-eyed subjects perceived tinnitus. This difference was not statistically significant (χ2(1) = 0.77; p = 0.38). Conclusion When exposed to reduced auditory stimulation, 3 out of 5 normal-hearing people are likely to experience tinnitus. However, there was no relationship between eye color and the perception of tinnitus in silence. Although melanin has been shown to play a role in the protection of the ear against noise trauma and the effects of age-related hearing loss, its role in the emergence of tinnitus needs further investigation.